2015
DOI: 10.1111/gtc.12281
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide identification of target genes of histone methyltransferase dG9a during Drosophila embryogenesis

Abstract: Post-translational modification of the histone plays important roles in epigenetic regulation of various biological processes. Among the identified histone methyltransferases (HMTases), G9a is a histone H3 Lys 9 (H3K9)-specific example active in euchromatic regions. Drosophila G9a (dG9a) has been reported to feature H3K9 dimethylation activity in vivo. Here, we show that the time required for hatching of a homozygous dG9a null mutant and heteroallelic combination of dG9a null mutants is delayed, suggesting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
0
10
2
Order By: Relevance
“…During the development of Drosophila , metamorphosis is also a process that flies use to tolerate starvation stress. Even though our study demonstrated that dG9a is important for starvation stress tolerance, the viability of the dG9a RG5 mutant was not significantly less than that of the wild-type during the pupal stage 21 , 22 . Together with our results showing that the viability of the dG9a RG5 mutant at the larval stage was not affected by fasting conditions, the function of dG9a for starvation stress appears to be specific to the adult stage.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…During the development of Drosophila , metamorphosis is also a process that flies use to tolerate starvation stress. Even though our study demonstrated that dG9a is important for starvation stress tolerance, the viability of the dG9a RG5 mutant was not significantly less than that of the wild-type during the pupal stage 21 , 22 . Together with our results showing that the viability of the dG9a RG5 mutant at the larval stage was not affected by fasting conditions, the function of dG9a for starvation stress appears to be specific to the adult stage.…”
Section: Discussioncontrasting
confidence: 70%
“…Three to five adult flies were dissected in PBS and fixed for 20 min in 4% paraformaldehyde at 25 °C. After permeabilization with 0.3% Triton X-100 in PBS, samples were incubated with primary antibodies specific for Atg8a (1:200, Novus Biologicals), dG9a (1:500, produced previously 40 ), or H3K9me2 (1/400, previously produced and used for Drosophila cells 22 , 42 ) at 4 °C for 16 h. After washing with 0.3% Triton X-100 in PBS, samples were incubated with the secondary antibody, Alexa Fluor 594 anti-mouse IgG (1:400, Molecular Probes) at 25 °C for 2 h. Samples were mounted with VECTASHIELD mounting media with DAPI (Vector Laboratories, Inc.). Intensity was only measured from nuclei in interphase and with a z-axis clearly present in their centers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…G9a mutant flies are fully viable [ 17 , 18 ] but do show phenotypic differences compared to wildtype flies. Loss of Drosophila G9a delays embryonic development [ 19 ]. In larval stages, G9a mutants show defects in the morphology of multidendrite neurons and have altered crawling behaviour [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Canton S was used as the wild-type strain. The dG9a RG5 flies were kindly provided by Dr. P. Spierer and used as the dG9a null mutant 52 . The dG9a RG5 flies show no defects in viability compared to Canton S in 1st instar larvae, pupae and adult stages 52 .…”
Section: Methodsmentioning
confidence: 99%